If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4e + 6 = -8 + 3e Reorder the terms: 6 + -4e = -8 + 3e Solving 6 + -4e = -8 + 3e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-3e' to each side of the equation. 6 + -4e + -3e = -8 + 3e + -3e Combine like terms: -4e + -3e = -7e 6 + -7e = -8 + 3e + -3e Combine like terms: 3e + -3e = 0 6 + -7e = -8 + 0 6 + -7e = -8 Add '-6' to each side of the equation. 6 + -6 + -7e = -8 + -6 Combine like terms: 6 + -6 = 0 0 + -7e = -8 + -6 -7e = -8 + -6 Combine like terms: -8 + -6 = -14 -7e = -14 Divide each side by '-7'. e = 2 Simplifying e = 2
| 41=c+2c-100 | | t/8.1+13.5=29.9 | | 2xdy-(4x^2+3y^2)dx=0 | | 3/4m-6/5=-7 | | 7.25=3.14x | | 1/3r=333 | | 3/4m-11/5=-7 | | x/22=-18+10 | | (7/4)x+x=22 | | 2x^2-16x+39=0 | | 5+2m-4=9m+9-6m | | 157-5x=4x+24 | | 9(t-4)+3t=6(2t+5)-10 | | 8x+7x=135 | | x*0.2=x-1000 | | y/16=-20 | | -15=2(y-3)-5y | | 15(5x-2/5)+32 | | 5/6x+4=7/10x | | 7/6z=1/14-11/15 | | e^4x+4e^2x-12=0 | | (5/13)x=35 | | 32x(x+5)=4800 | | m=0.4(20)+38 | | 30x(x+2)=3600 | | 4x^2-28x-32=0 | | 3.9q-4.3-3.3q=0.4q-3.3 | | 7x=27 | | 2x/3=32/6 | | 2x^3-7x^2-30x=0 | | I=(500)(0.13)(2) | | r(r+3)=70 |